(untitled) (Research, Society and Development, 2020)
In the current legal context, the discussion about aspects concerning the conditions of the Brazilian penitentiary system persists in contrast to the fundamental rights of incarcerated women, both in general and in their specific properties. In this sense, the objective of this article was to examine the concept and origin of the prison system, the penalty and the rights of the incarcerated individual, and how they are realized in the Brazilian social environment, aiming, with this, to understand the legal aspects related to the rights of the prisoner. imprisoned women and, finally, the specific factors about women in the prison system. In this perspective, the present article, by means of exploratory research, of qualitative nature, deductive method, collection of documental and bibliographic data, was developed in order to carry out a historical investigation on the theme, reaching the result that, although there are many advances regarding the fundamental guarantees provided to female citizens in Brazil, challenges, not only within the scope of Criminal Law, to be overcome for these people to fully exercise their human dignity.